Spiritual and Symbolic Diction as the Breath of Acep Zamzam Noor’s Poetry - Millatunnajiah; Nur Rizka Laila; Marsya Habibah Azzahra; Merdiyatna, Yang Yang (TALENTA, 2026)
This study aims to identify and analyze spiritual and symbolic diction in six poems by Acep Zamzam Noor: Aku Ini Doa, Cipasung, Sungai, Perasaan Sungai, Sendiri, and Angin dan Batu. Using a qualitative descriptive method with a structural and semiotic analysis approach, this research shows that Acep consistently employs diction that refers to spiritual, religious, and inner concepts. Words such as prayer, prayer mat, sky, and tears are not only used as aesthetic elements but also serve as symbols of contemplative experiences and the interconnectedness between humans, God, and the universe. Applying Riffaterre’s theory, it was found that the literal meanings of these words undergo displacement and distortion, thereby forming new, deeper meanings. The results of this study reinforce the understanding that Acep’s poetry is a silent dhikr flowing from profound spiritual awareness, making spiritual and symbolic diction the very breath of his poetic works.